PENGELOLAAN PEMBELAJARAN TEORI PRODUKTIF TEKNIK KENDARAAN RINGAN BERBASIS MULTIMEDIA DI SMK SATYA KARYA KARANGANYAR TAHUN AJARAN 2010 / 2011 - SUSANTO , EKO (2011)
The objectives of this research were: (1) describing the characteristics of teaching-learning plan of productive theory in otomotive class on the basis of multimedia in SMK Satya Karya Education Year 2010 / 2011 (2) describing the characteristics of teaching-learning process of productive theory in otomotive class on the basis of multimedia in SMK Satya Karya Karanganyar Education Year 2010 / 2011, (3) describing the characteristics of teaching-learning evaluation of productive theory in otomotive class on the basis of multimedia in SMK Satya Karya Karanganyar Education Year 2010 / 2011. This research employed the qualitative one. It was done during January 2011 up to May 2011. The design of the research is ethnographic research. The data were gained through observation, interview and documentation. The process of data analysis were; 1) data collection, 2) data reduction, 3) data display, and 4) data verification. While the results of the research were: 1) the teaching-learning plan of productive theory in otomotive class on the basis of multimedia in SMK Satya Karya included the making of syllabus and lesson plans. They were made by the teachers with the supervision of the headmaster, 2) the teaching-learning process of productive theory in otomotive class on the basis of multimedia in SMK Satya Karya were in four variables namely; teachers, students, teaching-learning process and product in the form of the students' ability improvement. The teachers had to be able to manage the four variables so that the process could run well, and 3) the evaluation had an important role in teaching-learning process. The evaluation was done in the forms of summative test and normative test.